Roles of irregularity of pore morphology in osteogenesis of Voronoi scaffolds: From the perspectives of MSC adhesion and mechano-regulated osteoblast differentiation - Lu, Teng; Sun, Zhongwei; Jia, Cunwei; Ren, Jiakun; Li, Jie; Ma, Zhiyuan; Zhang, Jing; Li, Jialiang; Zhang, Ting; Zang, Quanjin; Yang, Baohui; Yang, Pinglin; et al. (Journal of biomechanics, 2023)
Bone scaffolds designed based on the Voronoi-tessellation algorithm have been increasingly studied owing to their structural similarity with natural cancellous bone. The irregularity of pore morphology (IPM) influences the osteogenesis efficiency of Voronoi scaffolds since it may alter the static and hydromechanical microenvironments for the initial adhesion and mechano-regulated osteoblast differentiation (MrOD) of mesenchymal stem cells (MSCs). In this work, animal experiments were conducted to explore the relationship between IPM and osteogenesis efficiency in Voronoi scaffolds. A computational fluid dynamics (CFD) analysis based on discrete phase models was performed to predict the efficiency of MSC adhesion in different IPMs. Another combined finite element and CFD analysis based on the mechano-regulation algorithm was performed to predict the influence of IPM on the MrOD of the adhesive MSCs. The results showed that the osteogenesis efficiency of the Voronoi scaffolds increased as the IPM rose from low to moderate and then dropped as the IPM further rose. Same trends were also found in the MSC adhesion and MrOD, which caused by the changes of strain tensors on the strut surface and the tortuosity and fluid velocity of the fluid pathway. Moderate IPM induced the highest osteogenesis efficiency owing to its highest efficiencies of MSC adhesion and MrOD. This work identified the optimal IPM for the osteogenesis of Voronoi scaffolds and clarified its biomechanical mechanisms from the adhesion and mechano-regulated differentiation of MSCs, which is of great importance for guiding Voronoi scaffold design when it is used for bone defect repair.